2019
DOI: 10.1002/adfm.201904453
|View full text |Cite
|
Sign up to set email alerts
|

Photopatternable Nanolayered Polymeric Films with Fast Tunable Color Responses Triggered by Humidity

Abstract: Smart surfaces that can dynamically respond to environmental stimuli have demonstrated great promise in wearable electronics and optical detectors. Herein, a photopatternable nanolayered polymeric film that can reversibly display and hide structural colors in the visible range in response to relative humidity (RH) changes is reported. This film is fabricated on a silicon substrate using layer-by-layer assembly of chitosan and photoreactive carboxymethyl cellulose-azido derivative, and selectively crosslinked t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 50 publications
0
40
0
Order By: Relevance
“…Gan and co‐workers reported a photopatternable crosslinking strategy for invisible encryption based on a hydrogel interferometer of photoreactive carboxymethyl cellulose‐azido derivative. [ 98 ] The Bragg reflector was formed via layer‐by‐layer assembly of chitosan and a photoreactive cellulose. A masked UV irradiation led to crosslinked regions.…”
Section: Strategies For Anticounterfeiting Via Structural Colorsmentioning
confidence: 99%
“…Gan and co‐workers reported a photopatternable crosslinking strategy for invisible encryption based on a hydrogel interferometer of photoreactive carboxymethyl cellulose‐azido derivative. [ 98 ] The Bragg reflector was formed via layer‐by‐layer assembly of chitosan and a photoreactive cellulose. A masked UV irradiation led to crosslinked regions.…”
Section: Strategies For Anticounterfeiting Via Structural Colorsmentioning
confidence: 99%
“…[31][32][33][34] PCs, as dielectric materials with a periodic modulation for manipulating photons, have demonstrated great success and showed the potential for anti-counterfeiting applications. 272,[274][275][276][277][278][279][280][281] In this case, PC patterns were constructed by responsive materials, which could display two or multiple images by changing their colours and transforming between their appearance/disappearance in the background. Patterned PCs provide a new avenue for developing information security devices.…”
Section: Information Securitymentioning
confidence: 99%
“…18F). 277 Wang et al showed a novel anti-forgery pattern by a combination of the ''tricolourfluorescence'' property of carbon dots (CDs) and the unique microstructures constructed via a structured Si template or thermal treatment. Therefore, precisely assembled letter-shaped CD inverse opals (SiCDIOs) could be generated accordingly.…”
Section: Information Securitymentioning
confidence: 99%
See 2 more Smart Citations